(untitled) (AmS-Skrifter, 2020)
Investigations of the medieval harbour at the important royal manor of Avaldsnes, south-west Norway, revealed extensive underwater cultural layers and structures like ballast heaps and jetty foundations from the thirteenth until the early sixteenth century. The finds cover a large area and the conditions for preservation of the archaeological material is excellent. A waiting harbour at this strategic site along the fairway to Bergen probably got new functions and became the arena for intense activity during a 100-year period c. 1350–1450. The site known from written sources as Notau was most likely part of the same economic network as Bergen with ties to Hanseatic cities like Lübeck and Danzig. The pottery found on the sea bottom reveals an even wider range of international connections. The results have implications for the relationship between the Norwegian king and the Hanse and the Hanse’s activity outside of the medieval towns. The site is largely undisturbed by modern development and thus very well suited for future research.